Modeling of the Influence of Elevated Temperature on Oxygen Distribution in Soft Tissue - JASIŃSKI, Marek; ZADOŃ, Maria (Engineering Transactions, 2023)
The purpose of the study was to analyze the combined model of bioheat transfer and oxygen distribution in tissue during exposition to the external heat impulse. The effect of temperature and thermal damage to the tissue on the values of its thermophysical parameters was taken into account. The variable value of the perfusion coefficient affects the blood velocity in the capillary and thus the distribution of the partial oxygen pressure in the tissue. Various models of the oxygen dissociation curves were also considered and a sensitivity analysis was performed for the parameters of the oxygen distribution model. In the numerical realization stage, the finite difference method and the shooting method were used.